DEVELOPMENT OF A STATISTICAL PROGRAM FOR PEARSON CORRELATION ANALYSIS - BONINI NETO, Alfredo; BONINI, Carolina dos Santos Batista (Revista Brasileira de Engenharia de Biossistemas, 2011)
This paper presents the development of a graphical interface, i.e., an iterative program for the study of the Pearson correlation analysis between two variables. The main goal is make a simple program and easy to understand and that can be used in various application areas, including in the area of Biosystems Engineering. The correlation analysis shows the linear relationship between two variables (x, y) and the values will always be between -1 and +1. The sign indicates the direction, if the correlation is positive (growing linear regression) or negative (decreasing linear regression), and the size of the variable indicates the strength of the correlation between the variables x and y. The program was developed in Matlab environment that provides all possible commands for development.